Cloacal exstrophy variant in a female: A case report - Shelley Warner; Luciana Lerendegui; Monica D. Chow; David Lasko; Miguel Castellan; Felipe Pedroso (Elsevier, 2024)
Introduction: Cloacal exstrophy is a rare birth defect that affects both the genitourinary and gastrointestinal tract, with an estimated incidence between 1:200,000 and 1:400,000 live births. The exact mechanism that leads to this defect is still unknown. Our purpose is to report a case of omphalocele-exstrophy-imperforate anus-spinal defect (OEIS) complex with a rare variant to add to the literature. Case presentation: A 28-year-old female with no known medical history had a monochorionic diamniotic twin pregnancy. At 20 weeks of gestation a prenatal ultrasound demonstrated multiple fetal anomalies on twin B, including omphalocele, absent right kidney, non-visualization of bladder, and single umbilical artery. She had a scheduled Cesarean section at 34 weeks and 5 days of gestation. Twin B had a large omphalocele with an intact sac. Below the omphalocele, there was a cecal plate with a prolapsed ileum and a second small orifice corresponding to the hindgut. Two hemivaginas and hemiclitorises were appreciated inferior to the cecal plate but superior to a bladder plate bridge joining both halves. Each of the hemivaginas was connected to a hemiuterus with its own fallopian tube and ovary. The bladder was on both sides of the cecal plate and connected in the midline adopting a crescent shape with the concave side facing cephalad. Genetic testing confirmed an XX karyotype. On day-of-life 5 the patient underwent omphalocele repair and closure of the abdominal wall, tubularization of the cecal plate, and an end colostomy. Additionally, the hemivaginas and hemiclitorises were relocated to an orthotopic position and the bladder plates were joined together and used to cover part of the abdominal wall defect. She was discharged on day of life 42 with a weight of 2.72 kg. She continues to follow up outpatient. Her second stage procedure is still pending. Conclusion: The position of the genital tract superior to the bladder exstrophy observed in this case has not been described before and is not fully explained by the current theories on the development of OEIS.